Gender differences in the use of Personal Pronouns in the Moroccan Political Speech: A comparative Study of the pronominal choices of two Moroccan politicians - SADOUK, LAILA (Revue Internationale du Chercheur, 2021)
Sociolinguists have studied gender linguistic disparities intensively since the 1960s. The purpose of this article was to analyze the corpus of two speeches given by two Moroccan politicians from the same political party and determine whether there were any gender variations in the use of personal pronouns. The transcripts of four consecutive speeches were obtained from their original media outlets, translated into English, and evaluated using the text analysis tools Linguistic Inquiry and Word Count to determine how often the politicians used first-person pronouns. There were some slight but statistically significant variations in the use of personal pronouns between the sexes, according to the quantitative study. More nuanced disparities between the sexes were discovered in qualitative research, and they may be indicative of shifts in gender stereotyping as a result of language use.